The DrugAge database of aging‐related drugs. Issue 3 (16th March 2017) - Barardo, Diogo; Thornton, Daniel; Thoppil, Harikrishnan; Walsh, Michael; Sharifi, Samim; Ferreira, Susana; Anžič, Andreja; Fernandes, Maria; Monteiro, Patrick; Grum, Tjaša; Cordeiro, Rui; De‐Souza, Evandro Araújo; et al.
Summary: Aging is a major worldwide medical challenge. Not surprisingly, identifying drugs and compounds that extend lifespan in model organisms is a growing research area. Here, we present DrugAge (http://genomics.senescence.info/drugs/ ), a curated database of lifespan‐extending drugs and compounds. At the time of writing, DrugAge contains 1316 entries featuring 418 different compounds from studies across 27 model organisms, including worms, flies, yeast and mice. Data were manually curated from 324 publications. Using drug–gene interaction data, we also performed a functional enrichment analysis of targets of lifespan‐extending drugs. Enriched terms include various functional categories related to glutathione and antioxidant activity, ion transport and metabolic processes. In addition, we found a modest but significant overlap between targets of lifespan‐extending drugs and known aging‐related genes, suggesting that some but not most aging‐related pathways have been targeted pharmacologically in longevity studies. DrugAge is freely available online for the scientific community and will be an important resource for biogerontologists.